ANALISIS KELEMBAGAAN KEMITRAAN USAHA DI SENTRA SENTRA PRODUKSI SAYURAN (SUATU KAJIAN ATAS KASUS KELEMBAGAAN KEMITRAAN USAHA DI BALI, SUMATERA UTARA, DAN JAWA BARAT) - -, SAPTANA; INDRANINGSIH, KURNIA SUCI; HASTUTI, ENDANG L. (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 7, No. 3 November 2007)
ABSTRACT Economy globalization and commerce liberalization the competition of rivalization and integration of commodity market, that requires the change of operational method of stakeholder system of vegetable business. This research was aimed to analyze the comparation of system process among stakeholder business, in order to formulize the model of stakeholder system of vegetable business which compitable. The system of stakeholder business which exist and on going in the overall locations are: General Trade Pattern, Marketing Contract Pattern, Nucleus Estate Smallholder Pattern, Agribusiness Operational Cooperation Pattern, Seedling Credit and Supervision Pattern, Cooperation on Development of Agribusiness Sub Terminal, Cooperation on capital preparation of Multi Business, Village Credit System, Credit Union, and Banking Systems. The affectivity of business stakeholder system on vegetable commodity in production central area have not shown the optimum working effort yet, due to the weakness of commitment among those who involve in the cooperation, lack of open management, there was no market and price guarantee of all vegetable commodities, as well as lack of supply guarantee for supplier or stakeholder company important. Policy implication of the condition above were the necessary to build the stakeholder system of vegetable business which needed, strengthening, and profitable among each other. Keywords: Institution, Business Stakeholder, Central Production, Vegetable ABSTRAK Globalisasi ekonomi dan liberalisasi perdagangan mendorong terjadinya persaingan yang semakin kompetitif serta pasar komoditas yang terintegrasi, sehingga menuntut adanya perubahan cara beroperasinya kelembagaan-kemitraan usaha sayuran. Penelitian ini ditujukan untuk menganalisis pola, aturan main dan pola interaksi antar kelembagaan, serta analisis perbandingan kinerja kelembagaan antar kemitraan usaha, sehingga dapat dirumuskan model kelembagaan kemitraan usaha komoditas sayuran yang berdayasaing. Kelembagaan kemitraan usaha yang eksis dan sedang berjalan di seluruh lokasi antara lain adalah : Pola Dagang Umum, Pola Kontrak Pemasaran, Pola Inti-Plasma, Pola Kerjasama Operasional Agribisnis, Pola Pembinaan dan Kredit Bibit, Kerjasama dalam rangka pengembangan Sub Terminal Agribisnis (STA), Kerjasama dalam penyediaan modal Koperasi Serba Usaha (KSU), Lembaga Perkreditan Desa (LPD), Credit Union dan lembaga perbankan. Efektivitas kelembagaan kemitraan usaha pada komoditas sayuran di daerah sentra produksi belum menunjukkan kinerja yang optimal karena lemahnya komitmen antara pihak-pihak yang bermitra, manajemen yang kurang transparan, belum adanya jaminan pasar dan harga pada semua komoditas sayuran serta kurang adanya jaminan pasokan bagi supplier atau perusahaan mitra. Implikasi kebijakan penting dari kondisi di atas adalah pentingnya membangun kelembagaan kemitraan usaha komoditas sayuran yang dapat saling membutuhkan, memperkuat dan saling menguntungkan. Kata Kunci: Kelembagaan, Kemitraan Usaha, Sentra Produksi, Sayuran
Keywords: Institution, Business Stakeholder, Central Production, Vegetable (Kelembagaan, Kemitraan Usaha, Sentra Produksi, Sayuran)